“We don’t normally require that in other contexts, do we”: Interpersonal meanings of tag questions in British university seminars based on the BASE corpus - Wei, Lifang; Leung, Alex Ho-Cheong; Sun, Yufeng (Frontiers in Psychology, 2023)
This study investigates the use of canonical English tag questions used in the context of British university seminars. It aims to provide a comprehensive, corpus-based analysis for marked and unmarked forms and functions of anchor and tags. In so doing, it explores the interpersonal meanings expressed by tag questions from two dimensions: evidential modification of tags and conduciveness of responses, with illustrations of examples provided for specific contexts. Building upon this, an integrated diagram for the interpersonal meanings of tag questions in seminars is generated. The data for the study derives from seminars in the British Academic Spoken English (BASE) Corpus, which is herein both quantitative and qualitative analyzed. The findings reveal that three-quarters of tag questions in the data are utilized by teachers, though students also use tag questions from time to time. The unmarked form of tag questions in university seminars are generally positive-negative forms, with a few examples of negative-positive forms and very occasionally positive-positive forms. Moreover, this research finds that the default function of teachers’ tag questions in the data is to convey emphasis, followed by confirmatory function, with only a few cases of informational function. What’s more, in terms of responses, over 70% of tag questions are followed by no response, while less than 30% are followed by explicit responses. Accordingly, these findings raise the question of whether tag questions can really provide sufficient scope for interactions in classroom. It is hoped that this nuanced, corpus-based analysis of tag question utilization within the context of British university seminars would empirically reveal the interpersonal relations between teachers and students and thereby shed light on their efficient use of tag questions in seminar discussions.